Taḥlīl Ikhtibār al-Mahārah al-Kalām fī Kitāb al-‘Arabiyyah Bayna Yadaika al-Mujalladu fī Ḍaw‘i Tashnīfi Bloom lī Mustawa al-Majal al-Ma‘rifiy (Dirāsah Taḥlīliyah): Analysis of the Speaking Skills Test in the Book al-Arabiya Bayna Yadaika Volume 1 in Perspective f Bloom’s Taxonomy for Cognitive Domain Levels (an Analysis Study) - Ihwan Mahmudi; Neda Azzah Saniyyah; Dini Rofiatul Khoiriyah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2023)
In preparing for the test, teachers should be careful in using the appropriate type of test. Tests that are based on Bloom's taxonomy can help teachers measure students' deeper understanding of the material that has been studied. This study analyzes the speaking skill test in the Arabic book